Prepartum Dietary Supplementation of Potassium Humate Improves Postpartum Lactation Performance, Metabolic Profile of Multiparous Cows, and Immune Response of Their Calves - Cangir Uyarlar; Abdur Rahman; Eyup Eren Gultepe; İbrahim Sadi Cetingul; Muhammad Uzair Akhtar; Ismail Bayram (Animals)
This research was carried out to determine the effects of potassium humate on the lactation performance and metabolic parameters of dairy cows during the transition period. Potassium humate was added to the concentrate feed at the following levels: (a) control (0%), (b) 0.5%, (c) 1%, (d) 1.5%, and (e) 2% humas, during the dry period from −60 to 0 days until calving. The results indicated that the total milk yield after 305 days was higher in the 0.5% group than in the 2% humic acid group. The average daily milk yield from lactation was also greater in the 0.5% group than in the 2% humic acid group. In terms of metabolic health and blood biochemistry, lymphocytes, neutrophils, monocytes, NEFAs, and BHBA were different among the treatment groups. No effects were detected on the blood physiology parameters of the calves. The IgG concentration in the colostrum and serum of calves on day 1 and 2 were higher in the 0.5% and 1% humic acid groups, respectively, than in the other groups. Overall, adding humic acid, especially at the dose of 0.5%, to the concentrate feed of dairy cows during the dry period resulted in an increased postpartum milk yield for the cows and increased serum IgG in both the cows and calves, with decreased NEFAs on the calving day and decreased postpartum BHBA for cows.